2020
DOI: 10.18697/ajfand.89.18335
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin levels in seeds of commonly grown groundnut varieties (Arachis hypogaea L.) in Ghana as influenced by storage method

Abstract: Quality seeds of improved local genotypes is an important input for increasing the productivity of groundnut in Ghana. The existing means of meeting groundnut seed requirements, especially by smallholder farmers, have serious challenges with timely supply and access to these improved genotypes as a result of the limited participation of the private sector and the self-pollinated nature of the crop. Smallholder farmers who take the initiative to store their own seeds, have challenges with storage fungi and afla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a study conducted in the Ivory Coast in 2018, it was reported that all examined peanut butter samples had AFB1 contamination; 99.0% of the samples had AFB1 levels above 2 ppb, which is the EU limit, and concentrations reached a maximum of 4535 ppb [22]. In another study carried out in Ghana, it was found that peanuts sold in markets could contain AFB1 levels reaching 337 ppb [23]. Te presence of such high and varying amounts of AFs in food items is the result of diferences in the growing and storage conditions and agricultural practices suitable for the development of A. favus fungus.…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted in the Ivory Coast in 2018, it was reported that all examined peanut butter samples had AFB1 contamination; 99.0% of the samples had AFB1 levels above 2 ppb, which is the EU limit, and concentrations reached a maximum of 4535 ppb [22]. In another study carried out in Ghana, it was found that peanuts sold in markets could contain AFB1 levels reaching 337 ppb [23]. Te presence of such high and varying amounts of AFs in food items is the result of diferences in the growing and storage conditions and agricultural practices suitable for the development of A. favus fungus.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the suggestion that groundnuts dried on clean tarpaulin could reduce aflatoxin concentration compared to the traditional on-ground drying [21], it was recently shown that tarpaulin increased aflatoxin levels of three different varieties of groundnut during dried at two different locations in Ghana [31].…”
Section: Postharvest Drying Methods On Aflatoxin Occurrencesmentioning
confidence: 94%
“…Consequently in Ghana, aflatoxin occurrence in maize grains stored in jute sack was higher (about 55%) compared to grains stored in polyethylene sack [20]. This was also indicated for groundnut stored in jute sacks for 2 months that demonstrate a higher aflatoxin occurrences (148.21 ppb) than their counterpart stored in interlaced polyethylene jute sack [21]. Another study conducted in Tanzania to determine the occurrence of Aspergillus species and aflatoxin in maize stored in room (n = 32) and sacks (n = 8) showed that aflatoxin concentration was high in maize stored in room (334.33 μg/kg) than their counterpart stored in sacks (305.76 μg/kg) though the difference was not significant [22].…”
Section: Storage Methods On Aflatoxin Occurrencementioning
confidence: 94%
See 1 more Smart Citation